2013
DOI: 10.1093/ntr/ntt072
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Alternate Processes Contributing to the Association Between Maternal Smoking and the Smoking Behavior Among Young Adult Offspring

Abstract: introduction: Maternal smoking during pregnancy (MSP) is a known risk factor for regular smoking in young adulthood and may pose a risk independently of mother's lifetime smoking. The processes through which MSP exerts this influence are unknown but may occur through greater smoking quantity and frequency following initiation early in adolescence or increased sensitivity to nicotine dependence (ND) at low levels of smoking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 78 publications
3
21
0
Order By: Relevance
“…This difference in how long nicotine dependence predicts smoking frequency highlights the importance of early-emerging nicotine dependence symptoms in the etiology of regular smoking behavior: despite lower average nicotine dependence in the group of experimenters, those who reported nicotine-dependence symptoms at this very early stage of smoking were at high risk for more regular smoking in the future, even after conservatively accounting for concurrent smoking heaviness. For light smokers, who had already smoked more than 100 cigarettes at baseline, the weaker ability of nicotine dependence to predict smoking behavior into the future is consistent with previous findings of this sample that prior smoking behavior is the best predictor of future smoking behavior (Selya, Dierker, Rose, Hedeker, & Mermelstein, 2012; Selya et al, 2013). …”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This difference in how long nicotine dependence predicts smoking frequency highlights the importance of early-emerging nicotine dependence symptoms in the etiology of regular smoking behavior: despite lower average nicotine dependence in the group of experimenters, those who reported nicotine-dependence symptoms at this very early stage of smoking were at high risk for more regular smoking in the future, even after conservatively accounting for concurrent smoking heaviness. For light smokers, who had already smoked more than 100 cigarettes at baseline, the weaker ability of nicotine dependence to predict smoking behavior into the future is consistent with previous findings of this sample that prior smoking behavior is the best predictor of future smoking behavior (Selya, Dierker, Rose, Hedeker, & Mermelstein, 2012; Selya et al, 2013). …”
Section: Discussionsupporting
confidence: 88%
“…That is, the relationship between nicotine dependence and smoking frequency may be moderated by the stage of smoking, and not strictly time or age per se , with nicotine dependence being most predictive of long-term future smoking behavior when assessed early among very novice smokers. Once regular smoking patterns are established, however, prior smoking behavior becomes such a strong predictor of future smoking behavior (Selya, Dierker, Rose, Hedeker, & Mermelstein, 2012; Selya et al, 2013) that nicotine dependence becomes a weak or insignificant predictor. Early-emerging nicotine dependence assessed from novice smokers, then, may provide a special insight into one's initial sensitivity or susceptibility to nicotine dependence, while nicotine dependence assessed from more experienced smokers is likely to be conflated with the subsequent effects of smoking on nicotine dependence (Hu, Griesler, Wall, & Kandel, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, measures of postnatal environment are lacking, particularly exposure to secondhand smoke, which was not assessed in CPP. Although CPP mothers who smoked during pregnancy likely continued to smoke postpartum, several prior studies of MSDP and offspring smoking/ND have shown associations to be robust to control for postnatal secondhand smoke exposure (1417) and parental lifetime smoking status (111). Additional postnatal environmental factors (e.g., maternal care, parental sensitivity) have also been shown to mitigate effects of prenatal adversity (112–114).…”
Section: Discussionmentioning
confidence: 99%
“…47 Frequency of smoking is found to be a better predictor of the progression to regular smoking than ND for adolescents who are newer to smoking. 48 Defining smoking more broadly may therefore increase sensitivity to detect differences between treated and untreated youth.…”
mentioning
confidence: 99%